Recent Advances in End-to-End Automatic Speech Recognition (Invited Talk at ASC 2023) - Li, Jinyu (Microsoft, 2023)
This is the invited talk at APSIPA ASC 2023 for the Sadaoki Furui Prize Paper Award of the paper “Recent Advances in End-to-End Automatic Speech Recognition(opens in new tab)” is published APSIPA Transactions on Signal and Information Processing, 2022.